University teaching innovation through digital game-based learning: Pre-service teacher readiness for digital transformation in higher education - Candel, Elena Carrión; Berd-Gómez, Rachid; Freire, Manuel Ruiz; Martín, Ana María González (Journal of Education and e-Learning Research, 2025)
The use of game-based digital tools has become a highly relevant and dynamic element in the training of future educators, playing a pivotal role in shaping diverse teaching and learning processes. These tools offer a more engaging, effective, and interactive learning experience, designed to boost student motivation and provide immediate feedback. This study examines the impact of a didactic intervention using gamified digital tools (Genially, Quizizz, & WebQuest) on students’ learning and motivation in online university classrooms. The intervention was implemented over five months with future teachers (n = 262) enrolled in Early Childhood and Primary Education programs, as well as Music and Physical Education specializations at a private Spanish university. A design involving measurements before and after the intervention was employed to assess its impact, including an exploratory and a confirmatory factor analysis to validate the instrument’s three-dimensional structure. The findings confirm that the use of digital games enhances students’ perceptions of their own learning. Moreover, correlation analyses supported the robustness of the results, showing consistent relationships between the dimensions, while differences across age, gender, and degree type remained minimal or disappeared after the intervention. These results have practical implications for higher education, supporting the integration of such tools not only in music and physical education but across a range of curricular subjects.